2000
DOI: 10.1007/pl00014053
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cells engineered to secrete granulocyte-macrophage colony-stimulating factor using ex vivo gene transfer as vaccines for the treatment of genitourinary malignancies

Abstract: When irradiated and administered intradermally as vaccines, cancer cells engineered to secrete high levels of granulocyte-macrophage colony-stimulating factor (GM-CSF) by gene transfer elicit potent anticancer immune responses in a variety of animal tumor models. Upon vaccination, antigens present in the cancer cells are phagocytosed and processed by skin dendritic cells. These dendritic cells then prime anticancer immune responses by presenting antigenic peptides to T cells. The immune responses generated are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 0 publications
0
27
0
1
Order By: Relevance
“…Neutrophils (A) and macrophages (B) were counted and presented as average of total cell count ± SEM (n = 3). There was no significant difference between total neutrophil counts in PTEN −/− compared for viral therapy because there are various technically easy routes (e.g., transurethral, transperineal, and transrectal) for viral delivery (36). Here, the effect of oncolytic virus VSV(AV3), which replicates in IFN-defective cells, has been studied in the prostate-specific PTEN −/− mice model (20).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils (A) and macrophages (B) were counted and presented as average of total cell count ± SEM (n = 3). There was no significant difference between total neutrophil counts in PTEN −/− compared for viral therapy because there are various technically easy routes (e.g., transurethral, transperineal, and transrectal) for viral delivery (36). Here, the effect of oncolytic virus VSV(AV3), which replicates in IFN-defective cells, has been studied in the prostate-specific PTEN −/− mice model (20).…”
Section: Discussionmentioning
confidence: 99%
“…In a phase I clinical trial, seven of eight patients vaccinated with autologous irradiated, granulocyte macrophage colony-stimulating factor (GM-CSF)-secreting tumor cells mounted T-cell responses against the untransduced tumor cells (29). Due to the technical challenges of establishing autologous cell lines from surgically resected prostate cancer specimens, other clinical trials are now exploring the use of cytokine-secreting allogeneic tumor cell lines, including the LNCaP cell line, as cancer vaccines (30,31). Preliminary data from a phase I/II trial using the GVAX vaccine, a combination of GM-CSF-secreting LNCaP and PC-3 prostate lines, suggest a therapeutic benefit from this approach (31).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to biosafety concerns, this genetic modification method is preferable over a retroviral infection approach because retroviral infection involves risks of development of competent recombinant retroviral particles in vivo. K562-hGM-CSF cells secreted approximately 3000 ng per 10 6 cells every 24 h, which is higher than previously reported values that range from 42 to 1403 ng per 10 6 cells every 24 h. 19,22,41,42,44,45,47 Although the GM-CSF threshold for an effective immunostimulation effect has been evaluated to be 36 ng per 10 6 cells every 24 h, 48 there are no clearly defined values reported for the site of cell injection. On the other hand, Serafini et al 49 reported that a high-dose of GM-CSF could impair the immune response through the recruitment of myeloid suppressor cells.…”
Section: Discussionmentioning
confidence: 60%